2021
DOI: 10.3389/fpsyg.2021.640110
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Influential Factors on Readers' Continuance Intentions of E-Book APPs: Personalization, Usefulness, Playfulness, and Satisfaction

Abstract: With the rapid development of mobile devices, users can now read on the screen. Electronic reading (e-reading) has become a common reading style with the growth in online learning or electronic learning (e-learning). E-book applications (APPs) are widely developed and applied for reading on a screen. However, it is difficult for readers to change their reading habits or preference from paper-printed books to digital devices. The study of readers' continuance intention to use e-book APPs is the first step to im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 50 publications
6
23
0
10
Order By: Relevance
“…This finding was the same as that of the study of Roca and Gagné (2008), in which PEU can predict continuance intention. SN had a direct prediction to CIU, which was the same as the findings of other studies (Lee, 2010;Mouakket, 2015;Liu et al, 2021). In these studies, satisfaction was the only factor predicting CIU.…”
Section: Hypotheses Testingsupporting
confidence: 87%
“…This finding was the same as that of the study of Roca and Gagné (2008), in which PEU can predict continuance intention. SN had a direct prediction to CIU, which was the same as the findings of other studies (Lee, 2010;Mouakket, 2015;Liu et al, 2021). In these studies, satisfaction was the only factor predicting CIU.…”
Section: Hypotheses Testingsupporting
confidence: 87%
“…The emergence of communication technology and mobile devices has contributed to rapid developments in mobile applications (apps). Advances in network communication and mobile technology have considerably changed the lives and learning methods of people ( Nikou and Economides, 2017 ; Chao, 2019 ; Liu et al, 2021 ). Researchers ( Chao, 2019 ; Alshurideh et al, 2020 ; Hoi, 2020 ) have indicated that online learning combined with mobile technology is becoming an essential educational practice for teachers and students.…”
Section: Introductionmentioning
confidence: 99%
“…This study not only enhanced the technology acceptance model by introducing two variables, perceived enjoyment (Vladova et al, 2021) and satisfaction (You et al, 2020;Liu et al, 2021) in the original TAM, but also integrate TAM and WTP to explicit the factors affecting users' payment intention to online sports streaming. It was confirmed that satisfaction has a positive effect on payment intention to buy or subscribe to livestream sports broadcasts.…”
Section: Discussionmentioning
confidence: 99%
“…First, the sample was cross-sectional, which limited the ability to make causal inference. It is a dynamic and continuous process form users' payment intention to their actual purchase behavior, and then to the continuous intention of purchasing a product (Liu et al, 2021). Longitudinal study is warranted for future studies.…”
Section: Discussionmentioning
confidence: 99%